A high-resolution vegetation, fire, and climate history from the Aishihik Region, Yukon Territory, Canada - Ravindra, Rebecca (University of Ottawa (Canada), 2009)
Paleocological studies based on the analysis of lake sediments offer the potential for high resolution and well-dated records of past environmental conditions. A 2.7 m sediment core raised from Lake WA01 (unofficial name, 61°14'41"N, 136°55'35"W, 1000 m.a.s.l.) in the Aishihik region of the southwest Yukon Territory documents the post-glacial vegetation, fire, and climate history of the region surrounding the study site. The earliest portion of the WA01 pollen record was characterized by the establishment of open birch-shrub tundra at the study site. Picea glauca then established ca. 9,900 cal yrs BP, and has since remained dominant on the landscape Progressively decreasing precipitation in the region over the last ca. 9,000 years, noted in a previous study by Viau et al. (2008), is not captured in the Lake WA01 climate reconstructions. From ca. 9,900 cal yrs BP to the present day, reconstructed mean July temperatures and total annual precipitation at the study site remained essentially constant. A short period of low total annual precipitation is noted from deglaciation at 10,500 cal yrs BP to 9,900 cal yrs BP. The regional-scale fire regime surrounding the study site increased gradually in intensity over the course of the Holocene. Local fires in the area immediately surrounding the study lake decreased gradually in frequency and/or size over the course of the Holocene, though the exact cause remains unclear. An alternating pattern in the sediment loss-on-ignition from Lake WA01 is related to similar trends in □18O values from the Mount Logan oxygen isotope record (Fisher et al., 2008). Based on a positive association between sediment carbonate content and enriched □18O values from the Mount Logan record, it is proposed that periods of increased and decreased sediment carbonate content in the WA01 core are indicative of wetter and drier conditions at the study site, respectively.
Keywords: Geography.